2012
DOI: 10.1002/chem.201102687
|View full text |Cite
|
Sign up to set email alerts
|

Observations and Descriptions versus Explanations—An Example: Does Nature, Does Theory Know About Steric Hindrance?

Abstract: Quantum chemical investigations in the literature sometimes underpin traditional chemical concepts (such as those of different primary and secondary types of chemical bonding or of steric repulsions) but sometimes also seem to undermine them. Conceptual pitfalls in recent discussions in this and other leading journals, when combining empirically and quantum chemically based reasoning, can be avoided when taking four points into account: 1) The construction of theoretical concepts should be guided by both, phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
1
4

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 91 publications
1
23
1
4
Order By: Relevance
“…They found that 1,2-diaminobenzene is 3.0 kJ Á mol À1 more stable than 1,3-diaminobenzene and 13.1 kJ Á mol À1 more stable than 1,4-diaminobenzene. Although the results obtained by QTAIM (figure 3) did not reveal any critical point between the hydrogen atoms and the nitrogen atoms of the amino groups in ortho positions, indicating no intramolecular bonds in 4,5-diaminopyrimidine, 2,4,5-triaminopyrimidine and 4,5,6-triaminopyrimidine, the energetic results for diaminobenzenes [54] and the structural results in this work show that there is a complicated balance between attraction and stereochemical hindrance [55] when two amino groups are in ortho positions (figure 3) which results in a small enthalpic stability [54]. Krueger [56] studied deuterated 1,2-diaminobenzene by infrared spectroscopy and concluded that a double NÀHÁ Á ÁN hydrogen bond (figure 3) exists between the two amino groups and Estácio et al [57] have justified the enthalpic difference between the para and ortho isomers of diaminobenzene in terms of intramolecular hydrogen bonds.…”
Section: Aromaticity and Conjugationcontrasting
confidence: 62%
“…They found that 1,2-diaminobenzene is 3.0 kJ Á mol À1 more stable than 1,3-diaminobenzene and 13.1 kJ Á mol À1 more stable than 1,4-diaminobenzene. Although the results obtained by QTAIM (figure 3) did not reveal any critical point between the hydrogen atoms and the nitrogen atoms of the amino groups in ortho positions, indicating no intramolecular bonds in 4,5-diaminopyrimidine, 2,4,5-triaminopyrimidine and 4,5,6-triaminopyrimidine, the energetic results for diaminobenzenes [54] and the structural results in this work show that there is a complicated balance between attraction and stereochemical hindrance [55] when two amino groups are in ortho positions (figure 3) which results in a small enthalpic stability [54]. Krueger [56] studied deuterated 1,2-diaminobenzene by infrared spectroscopy and concluded that a double NÀHÁ Á ÁN hydrogen bond (figure 3) exists between the two amino groups and Estácio et al [57] have justified the enthalpic difference between the para and ortho isomers of diaminobenzene in terms of intramolecular hydrogen bonds.…”
Section: Aromaticity and Conjugationcontrasting
confidence: 62%
“…[11,27] And conversely, the concept of unperturbed overlapping atoms [23] supplies insight into unexpected results from the QTAIM approach. [21,28,29] Appendices Appendix A: Relation between bonded and transferable radii Let there be given a cations A + and x anions X À , forming altogether a·x polar diatomic molecules AX with a·x different observable bond lengths D AX . They can be partitioned into 2·a·x observable bonded radii [Eq.…”
Section: Conclusion and Summarymentioning
confidence: 99%
“…They appear more or less accidentally and seem to have no specific meaning when they just show up at equilibrium bond lengths. Similarly, there may occur bond paths in the electron density distribution sometimes rather accidentally, indicating the near-formation of a bond, or just a non-bonded contact, looking from various chemical points of view [75,76].…”
Section: W H Eugen Schwarzmentioning
confidence: 99%